Purification and Substrate Specificities of Two α-l-Arabinofuranosidases from Aspergillus awamori IFO 4033 - Kaneko, Satoshi (American Society for Microbiology, 1998)
α-l-Arabinofuranosidases I and II were purified from the culture filtrate of Aspergillus awamori IFO 4033 and had molecular weights of 81,000 and 62,000 and pIs of 3.3 and 3.6, respectively. Both enzymes had an optimum pH of 4.0 and an optimum temperature of 60°C and exhibited stability at pH values from 3 to 7 and at temperatures up to 60°C. The enzymes released arabinose from p-nitrophenyl-α-l-arabinofuranoside, O-α-l-arabinofuranosyl-(1→3)-O-β-d-xylopyranosyl-(1→4)-d-xylopyranose, and arabinose-containing polysaccharides but not from O-β-d-xylopyranosyl-(1→2)-O-α-l-arabinofuranosyl-(1→3)-O-β-d-xylopyranosyl-(1→4)-O-β-d-xylopyranosyl-(1→4)-d-xylopyranose. α-l-Arabinofuranosidase I also released arabinose from O-β-d-xylopy-ranosyl-(1→4)-[O-α-l-arabinofuranosyl-(1→3)]-O-β-d-xylopyranosyl-(1→4)-d-xylopyranose. However, α-l-arabinofuranosidase II did not readily catalyze this hydrolysis reaction. α-l-Arabinofuranosidase I hydrolyzed all linkages that can occur between two α-l-arabinofuranosyl residues in the following order: (1→5) linkage > (1→3) linkage > (1→2) linkage. α-l-Arabinofuranosidase II hydrolyzed the linkages in the following order: (1→5) linkage > (1→2) linkage > (1→3) linkage. α-l-Arabinofuranosidase I preferentially hydrolyzed the (1→5) linkage of branched arabinotrisaccharide. On the other hand, α-l-arabinofuranosidase II preferentially hydrolyzed the (1→3) linkage in the same substrate. α-l-Arabinofuranosidase I released arabinose from the nonreducing terminus of arabinan, whereas α-l-arabinofuranosidase II preferentially hydrolyzed the arabinosyl side chain linkage of arabinan.